Еxtracellular matrix as a cellular information microenvironment - L. A. Naumova; V. A. Starodumova (Бюллетень сибирской медицины)
The article discusses modern ideas about the role of extracellular matrix (ECM) and cellular elements of connective tissue (CT) in tissue homeostasis in normal and pathological conditions. The works of recent years reflect a shift of interests concerning the study of many pathological processes, particularly carcinogenesis, to the state of the ECM and CT cells, which are considered as active components of the tissue that determine the processes of cellular proliferation, differentiation, migration, and apoptosis. The most important properties of the ECM attracting the attention of researchers include mechanotransduction, leading to the activation of cytoskeletal mechanisms and various cell signaling pathways; modeling of the effects of various cytokines, growth factors, and hormones; maintenance of the stem cell niches; influence on the emergence and course of the tumor process, in particular, formation of a cancerized field and premetastatic niches; and the epithelial-mesenchymal transition (EMT). Currently, CT cells are also an important object of study, in particular, fibroblasts, which are the main producers of ECM components. The attention of researchers is directed primarily to cancer-associated fibroblasts, the phenotype of which forms in the tissue long before the tumor appears. New knowledge about the role of ECM and CT cells in tissue homeostasis determines new approaches to treatment of many diseases, such as systemic sclerosis, tumors, etc.